Fabrication, photoresponse and temperature dependence of n-VO2/n-MoSe2 heterojunction diode. (June 2019) - Patel, Abhishek; Pataniya, Pratik; Solanki, G.K.; Sumesh, C.K.; Patel, K.D.; Pathak, V.M.
Abstract: Transition metal dichalcogenides are being interest in study for their optoelectronic device applications. This is an upsurge in research efforts after realizing monolayer device structures. This article presents the use of vanadium dioxide phase transition from monoclinic to rutile for obtaining heterojunction to Schottky diode characteristic transition. IV characteristics of VO2 /MoSe2 heterojunction diode has studied in the temperature range 303 K–343 K. The results reveal the rectifying nature of the junction at 303 K. As temperature increases, rectification decreases and swings towards Schottky junction characteristics due to MIT behaviour of VO2 thin film. The heterojunction has also investigated in dark condition and under the photo intensity ranging from 10 to 60 mW/cm 2 . The pronounced rise in forward and reverse current was observed when the junction was exposed under the light. The typical diode parameters such as ideality factor, saturation current, Richardson constant, and responsivity (R), sensitivity (S) and detectivity (D) are determined for the quantitative analysis of VO2 /MoSe2 heterojunction. IV characteristics of the diode resemble to photodiode IV characteristics. Highlights: The VO2 /n-MoSe2 hetero junction diode has been fabricated by DVT and thermal evaporation techniques respectively. Prepared device has been haracterized under the effect of temperature and incident illumination intensity. Diode parameters, responsivity, sensitivity and detectivity were measured from the I-V characteristics. Diode confirms tuneable rectification with respect to rising temperature and incident illumination intensityremovebond. I-V characteristics in reverse bias seems like photodiode characteristics.